THE EFFECT OF TQM IMPLEMENTATION AND PRODUCTION EFFECTIVENESS ON SKINTIFIC SKINCARE CUSTOMER SATISFACTION IN MEDAN CITY - Iman Putra Jaya Hulu; Anggi Dian Safitri; Putri Nabila; Irwan Nopian Sinaga (CV Naskah Aceh, 2025)
This study aims to determine the influence of Total Quality Management (TQM) and production effectiveness on Skintific customer satisfaction in Medan City. The method used was quantitative associative with 75 Gen Z respondents. The results showed that TQM and production effectiveness had a significant effect both partially and simultaneously on customer satisfaction, with t-calculated values of 8.383 and 6.145 respectively (t table = 1.66071), and F calculated as 51.594 (F table = 3.12). The Adjusted R² value of 0.578 shows the contribution of the two variables of 57.8% to customer satisfaction. In conclusion, improving overall quality and efficient production processes can increase customer satisfaction in the skincare industry.